The clash of civilizations and the remaking of world order - Huntington, Samuel P. (New York, NY : Simon & Schuster, 1997)
In this text, the author argues that as people increasingly define themselves by ethnicity and religion, the West will find itself more and more at odds with non-western civilizations that reject its ideals of democracy, human rights, liberty, the rule of law, and the separation of the church and state. Picturing a future of accelerated conflict and increasingly "de-Westernized" international relations, this text further argues for greater understanding of non-western civilizations and offers strategies for maximizing Western influence.

Picturing a future of accelerated conflict between civilizations threatening to dominate world politics, this classic study of the post-Cold War situation argues that an international order based on civilizations is the best safeguard against war.
Reprint. Originally published: 1996.
"A Touchstone book."
Includes bibliographical references (p. [323]-352) and index.
oif 06/03/15
Loan
Keywords: World politics -- 1989-; Post-communism.; Civilization, Modern -- 1950-; International relations -- Forecasting; Culture conflict